Risk factors of adult Dengue Fever in urban community of Nepal - Harishchandra Shah; Basu Dev Pandey (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2021)
With the objectives of determining the association between risk factors and Dengue Fever (DF), a case-control study with a random sample size of 102:102 in each was conducted at Hetauda and Kamalamai Municipalities, Nepal. The hypothesis of risk factors for DF like low level of knowledge about DF, discarded receptacles, old tires, containers, etc. nearby house, and use of stagnant AC/Coolers was used to conduct the study. Traveling to DF affected areas nearly 2 weeks before the onset of disease was significantly associated with dengue fever (OR= 6.10, 95% cl: 1.31-28.34, p<0.021). Waste disposal of old containers, receptacles, tires during the rainy season were significantly associated with the incidence of DF (AOR= 6.308, 96% cl: 2-751-14.462, p<0.000). The frequency of DF was associated with the middle social class level (p<0.05, d. f. 2). Uncovered water tanks of the household were significantly associated with DF (AOR= 3.78, 95% cl: 1.51-9.45, p<0.0043). As the number of families increases in the household, the number of cases increases with a positive correlation (r = +0.62). Crowded households with more than 2 occupants in one room were at risk of dengue infection. The study concluded that DF was associated with the risk factors of traveling to endemic areas, discarded waste containers, receptacles, tires, and uncovered water tanks, middle social class, and crowded households. Public health managers should prioritize these risk factors while planning for DF control and prevention.